PENTINGNYA PENGATURAN DELIK PERDAGANGAN PENGARUH (TRADING INFLUENCE) PADA UNDANG-UNDANG TINDAK PIDANA KORUPSI DI INDONESIA - Mulyono Dwi Purwanto; Tuti Widyaningrum (Jurnal Kajian Ilmiah, 2023)
The event of democracy in Indonesia will soon occur in 2024. Related to that, the offense of Trading in Influence will arise with the existence of corruption committed by officials/State Organizers and other related parties accompanied by bribery due to having that power/influence. However, this offense does not yet exist in the existing and clearly regulated corruption law. The offense of trafficking in influence is contained in the law resulting from the ratification of the United Nations Convention Against Corruption (UNCAC) in 2003. Since it does not yet exist, the offense of bribery and/or gratification is used which is in accordance with the facts that occurred and was indicted by the Public Prosecutor. The judge decides according to what was indicted and the facts revealed at trial. So that there is a need for a criminal offense or criminalization of trading in influence and its legal arrangements in corruption in Indonesia. The method used is normative juridical with an approach to legislation, conceptual and case from existing secondary data from corruption cases that occurred in the Corruption Court's decision at the Central Jakarta District Court. So by setting up an independent influence trade offense, in addition to taking firmer action, it also prevents the occurrence of the corruption offense through detailed rules and heavier sanctions as well as law enforcement without favoritism/selectiveness that is carried out consistently so that legal objectives are obtained in the form of legal certainty. and justice. Keywords: Influence Trading, Legal vacuum, Law enforcement.